The dipeptidyl peptidase‐4 inhibitor linagliptin lowers postprandial glucose and improves measures of β‐cell function in type 2 diabetes1. Issue 10 (9th June 2014) - Heise, T.; Larbig, M.; Patel, S.; Seck, T.; Hehnke, U.; Woerle, H.‐J.; Dugi, K.
<x xml:space="preserve">Abstract</x> Progressive deterioration of pancreatic β‐cell function in patients with type 2 diabetes mellitus (T2DM) contributes to worsening of hyperglycaemia. To investigate the effects of the dipeptidyl peptidase‐4 inhibitor linagliptin on β‐cell function parameters, a pooled analysis of six randomized, 24‐week, placebo‐controlled, phase 3 trials of 5 mg of linagliptin daily was performed in 2701 patients with T2DM (linagliptin, n = 1905; placebo, n = 796). At week 24, observed improvements in HbA1c, fasting plasma glucose, and 2‐h postprandial glucose were significantly greater for linagliptin than placebo (all p < 0.0001). Homeostasis model assessment (HOMA)‐%β, as a surrogate marker of fasting β‐cell function, was significantly improved with linagliptin, and did not change with placebo (placebo‐adjusted mean ± s.e. change for linagliptin: 16.5 ± 4.6 (mU/l)/(mmol/l); p = 0.0003). Further study is required to determine if the significant improvement in HOMA‐%β with linagliptin will translate into long‐term improvements in β‐cell function.